Novel Microsatellite Markers for Brazilian Mangrove Oysters ( Crassostrea gasar ) and their Cross-Amplification in Crassostrea rhizophorae - Renata do Socorro Corrêa Baldez; Mauro André Damasceno Melo; Iracilda Sampaio; Claudia Helena Tagliaro (Brazilian Archives of Biology and Technology, 2016)
ABSTRACT A microsatellite CT/GT enriched genomic library was developed for Crassostrea gasar and twelve new polymorphic loci were isolated and characterized. The markers were successfully amplified from 25 individuals of Crassostrea gasar and 11 cross-amplified individuals of Crassostrea rhizophorae. There was no evidence of linkage between loci in either species.